INTEGRASI TAJHIZUL MAYIT DALAM KURIKULUM EKSTRAKULIKULER SEBAGAI UPAYA PENGUATAN PENDIDIKAN KARAKTER ISLAMI - Siregar, Syamsiah Depalina; Lubis, Fatwa Aulia; Syofyan, Heri; Lubis, Aswar Anas; Dly, Ainun Adilah; Hairani, Aisyah; Nurjamilah, Nurjamilah; Pulungan, Nur Jannah (CV. Denasya Smart Publisher, 2025)
The care of the dead in Islam is a fardhu kifayah obligation that every Muslim must know. However, awareness and understanding of the procedures of Tajhizul Mayit is still limited, especially among students. This study aims to integrate Tajhizul Mayit learning into the extracurricular curriculum at SMK Negeri 1 Panyabungan through lecture, demonstration, and hands-on practice methods. This activity involved 27 learners with an approach of initial observation, program design, and competency evaluation. The results showed that students experienced an increase in understanding and skills in taking care of the dead according to the guidance of Islamic law. In addition, this program also forms Islamic character, increases empathy, and social care of students. Although there were obstacles such as the lack of availability of practical tools, collaboration efforts with donors and social institutions succeeded in overcoming these obstacles. Positive responses from students and school administrators indicate that this program deserves to be a permanent part of extracurricular activities to increase the awareness and readiness of the younger generation in carrying out religious social responsibilities.